Boron adsorption and leaching in a Brazilian Oxisol - Rosolem, Ciro Antonio; Bíscaro, Thaís (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate soil boron dynamics in a Typic Hapludox cropped with soybean for three years, as affected by boron rates and liming. Soil samples were taken during three years from a field experiment with lime rates of 0, 1.5, 3, 4.5, 6, 7.5 and 9 Mg ha-1 and boron rates of 0, 1, 3, 5, 7 and 10 kg ha-1. Boron adsorption isotherms as affected by liming and time under cropping were determined. Boron leaching, as affected by boron fertilization and liming was also evaluated. When lime was applied, even at high rates, soil boron adsorption was very high only in the first year, and decreased with time. Boron leaching, though not affected by liming, is strongly related to soil boron contents and boron fertilization.
Keywords: boric acid; fertilization; liming; micronutrients